Gastrointestinal Dysfunction in Multiple Sclerosis and Related Conditions - Sakakibara, Ryuji (Seminars in Neurology, 2023)
Nervous system disorders may be accompanied by gastrointestinal (GI) dysfunction. Brain lesions may be responsible for GI problems such as decreased peristalsis (e.g., lesions in the basal ganglia, pontine defecation center/Barrington's nucleus), decreased abdominal strain (e.g., lesions in the parabrachial nucleus), hiccupping and vomiting (e.g., lesions in the area postrema), and appetite loss (e.g., lesions in the hypothalamus). Decreased peristalsis also may be caused by lesions of the spinal long tracts or the intermediolateral nucleus projecting to the myenteric plexus. This review addresses GI dysfunction caused by multiple sclerosis, neuromyelitis optica spectrum disorder, and myelin oligodendrocyte glycoprotein-associated disorder. Neuro-associated GI dysfunction may develop concurrently with brain or spinal cord dysfunction or may predate it. Collaboration between gastroenterologists and neurologists is highly desirable when caring for patients with GI dysfunction related to nervous system disorders, particularly since patients with these symptoms may visit a gastroenterologist prior to the establishment of a neurological diagnosis.
Keywords: gastrointestinal dysfunction; multiple sclerosis; neuromyelitis optica spectrum disorder; myelin oligodendrocyte glycoprotein-associated disorder